2014
DOI: 10.1007/s10534-014-9744-5
|View full text |Cite
|
Sign up to set email alerts
|

Delta-lactoferrin induces cell death via the mitochondrial death signaling pathway by upregulating bax expression

Abstract: Delta-lactoferrin (∆Lf) is a transcription factor belonging to the lactoferrin family, the expression of which inhibits cell proliferation and leads to Skp1 and DcpS gene transactivation. In this study, we showed that ∆Lf expression also induces cell death via apoptosis in HEK 293 and MCF7 cells using a cell viability assay and DNA fragmentation. Western blot analyses showed that apoptosis was caspase-9, 7 and 8 dependent. Proteolytic cleavage of the endonuclease PARP was significantly increased. The levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These interplays offer theoretically infinite combinations of PTMs on protein isoforms in the human proteome. The diversity of O ‐GlcNAcylated proteins, the dynamism of O ‐GlcNAcylation and its interaction with other PTMs make this glycosylation a regulator of most of the basic and fundamental cellular processes such as cell signaling , cell cycle , and apoptosis . Deregulation of O ‐GlcNAc cycling has been linked with the etiology of diabetes , cancers , cardiovascular diseases , and neuronal disorders .…”
Section: O‐glcnac In the World Of Ptmsmentioning
confidence: 99%
“…These interplays offer theoretically infinite combinations of PTMs on protein isoforms in the human proteome. The diversity of O ‐GlcNAcylated proteins, the dynamism of O ‐GlcNAcylation and its interaction with other PTMs make this glycosylation a regulator of most of the basic and fundamental cellular processes such as cell signaling , cell cycle , and apoptosis . Deregulation of O ‐GlcNAc cycling has been linked with the etiology of diabetes , cancers , cardiovascular diseases , and neuronal disorders .…”
Section: O‐glcnac In the World Of Ptmsmentioning
confidence: 99%
“…1 The O-GlcNAc modification is nutrient sensitive, 2 and part of a signaling network that plays key roles in many fundamental biological processes, including signal transduction 3-5 epigenetic regulation, 6,7 stress response, 8,9 and protein degradation, 10,11 and apoptosis. 12,13 Only two human enzymes, O-GlcNAc transferase (OGT) 14,15 and OGA 16 are responsible for the addition and removal of O-GlcNAc, respectively. Aberrant O-GlcNAc profiles have been suggested to play a mechanistic role in the etiology and pathological progression of several diseases, including diabetes, [17][18][19] cancers, [20][21][22] and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Two regions of Lf in which a strong concentration of positive charges were found could be good candidates [ 10 ]. ΔLf exhibits antitumoral activities and we previously showed that overexpression of ΔLf leads to cell cycle arrest at the G1/S transition and apoptosis [ 11 , 12 ]. ΔLf mainly exerts its anti-proliferative and pro-apoptotic activities via its role as a transcription factor.…”
Section: Introductionmentioning
confidence: 99%
“…ΔLf mainly exerts its anti-proliferative and pro-apoptotic activities via its role as a transcription factor. Indeed, ΔLf transactivates different target genes such as Skp1 , DcpS , Bax , SelH , GTF2F2 and UBE2E1 [ 9 , 12 14 ]. A genome-wide pathway analysis and our quantitative proteomic analysis showed that the re-introduction of Lf isoforms in cancerous cells modified essential genes and/or signaling networks responsible mainly for cell survival, apoptosis and RNA processing [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%